Efisiensi Sistem Pemanasan Air dengan Penerapan Selubung Bertingkat pada Perforated Burner - Agung Sugeng Widodo; Francisca Gayuh Utami Dewi (Jurnal Rekayasa Mesin, 2018)
One of the causes of inefficiency in the heating system by using a gas stove is radiation heat transfer. The application of stratified sheath is expected to reduce the heat loss. In this study an investigation conducted on a gas stove type perforated burner, by adding a stratified sheath. The parameters such as energy absorbed by water and energy produced by fuel are used to measure the performance of the heating system. The fuel is liquid petroleum gas (LPG) with a composition of 50% butane and 50% propane. The results show that the application stratified sheath on perforated burner at 0,0125 liter / sec has an average efficiency of 53,2% with the time required to boil 1,5 liters of water for 670 seconds, 36 seconds faster for the case perforated burner without stratified sheath and 80 seconds faster than conventional burner cases.